Efficacy of 810 nm diode laser in hair reduction in Indian subpopulation using a novel Gabor filter‐based detection software and hair algorithm. (13th December 2021) - Pai, Sathish B.; Suvarna, Punya; Shetty, Varsha M.; Pathan, Sameena
Abstract: Background: Diode laser (810 nm) is frequently employed for hair reduction. There are few studies determining the efficacy in Indian population. Objectives: Assessment of efficacy and safety of 810 nm diode laser in facial/axillary hair reduction and objective assessment of the improvement with dermoscopy, photographs, and novel Gabor filter‐based hair detection algorithm. Methodology: This hospital‐based study included 40 adult women with 108 treatment sites over 5.4 sessions (range 4–8). Evaluation of treatment areas (hair texture, density) was done using modified Ferriman–Galwey scoring. Photography and dermoscopic images were taken before each session and 6 weeks after the last. Immediate and delayed adverse reactions were noted. Assessment of efficacy was done by patient, principal, and blinded investigator using Global Aesthetic Improvement scale (GAIS) and hair detection algorithm (evaluating characteristics of dermoscopic hair). Results: The fluences ranged from 16 to 29 Joules/cm 2 with pulse width of 30 ms. Upper lip ( n  = 29, 26.9%) and chin ( n  = 25, 22.1%) were commonly treated areas. Improvement in hair texture and density (reduction in uniformly distributed, terminal hair from 37.1% to 13.9%) was statistically significant ( p  < 0.0001) . Excellent improvement of 75–100% (GAIS) was noted by principal and blinded investigator in 24.1% and 33.3% total sites, respectively. The median improvement, calculated by the algorithm, was 60% for side locks, 53.9% for axilla, 24.1% for upper lip, and 14.9% for chin. Axilla and upper lip were sites associated with maximum discomfort. Epidermolysis and paradoxical hypertrichosis were seen in five patients each. Conclusion: The 810 nm diode laser is safe and effective in the reduction of dark, coarse terminal hairs in Fitzpatrick skin types III–V. Inter‐observer variation and investigator bias in the assessment of efficacy can be successfully overcome by using the algorithm.